Storage stability of biofuel - Varman, M.; Masjuki, Haji Hassan; Cheah, M.Y.; Cheng, Y.H.; Kalam, M.A.; Liaquat, A.M.; Shahabuddin, M.; Mofijur, M. (2012)
Biofuel is one of the prime candidates to take over the role played by fossil fuel as the main source of energy in the future. Numerous studies have been done on the potential of biofuel to produce similar power output generated by the current petrol and diesel which are depleting without any drawbacks. The objective of this particular study is to investigate 4 of the more established vegetable oil in the energy industry namely jatropha, palm, coconut and canola oil in terms of storage stability of biofuel at room temperature and 80ºC. The biofuels were tested in terms of density, kinematic viscosity, Total Acid Number (TAN), flash point and oxidation stability every 2 weeks for 10-12 weeks or 3 months at 2 different temperatures to obtain a conspicuous result. At the end of the experiment and test, it is found that palm oil is the biofuel with the best storage stability. The next biofuel that followed is jatropha oil, canola oil and finally coconut oil. Although palm oil showed poor kinematic viscosity, however it has good stability in terms of density, Total Acid Number (TAN) and also relatively stable oxidation and flash point in comparison with the 4 samples tested. The experiment result and data also showed that effect of continuous heating at 80ºC promotes oxidation process, higher Total Acid Number (TAN), lower flash point as well as increase in density and kinematic viscosity.